2009
DOI: 10.1002/bdm.635
|View full text |Cite
|
Sign up to set email alerts
|

Framing of imprecise quantities: When are lower interval bounds preferred to upper bounds?

Abstract: Imprecisely known quantities (e.g., predictions) are often described in approximate terms as ''more than X'' or ''less than Y'' (e.g., ''Ann will earn more than $50 000'' or ''less than $60 000''). Such phrases carry both quantitative and qualitative (pragmatic) information. Three studies are reported showing that lower limit estimates (more than, over, minimum) are generally more frequent, and considered more appropriate than upper limit estimates (less than, under, maximum) over a wide range of contexts. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…The corpus counts indicate that lower‐limit phrases (over and more than) are more common with probabilities above than below 50%, whereas upper‐limit phrases (under and less than) occur primarily in a context of low probabilities. Additionally, “more than” phrases are generally more frequent than “less than” phrases, as has been found previously in other domains (amounts of money, estimates of time and distances, Halberg & Teigen, , and comparative statements, Hoorens & Bruckmüller, ). In addition, 50% stands out as particularly prominent number, reminiscent of the “50% blip” found in lay chance estimates (Fischhoff & Bruine de Bruin, ).…”
Section: Single‐bound Probability Statements In Everyday Discoursesupporting
confidence: 78%
“…The corpus counts indicate that lower‐limit phrases (over and more than) are more common with probabilities above than below 50%, whereas upper‐limit phrases (under and less than) occur primarily in a context of low probabilities. Additionally, “more than” phrases are generally more frequent than “less than” phrases, as has been found previously in other domains (amounts of money, estimates of time and distances, Halberg & Teigen, , and comparative statements, Hoorens & Bruckmüller, ). In addition, 50% stands out as particularly prominent number, reminiscent of the “50% blip” found in lay chance estimates (Fischhoff & Bruine de Bruin, ).…”
Section: Single‐bound Probability Statements In Everyday Discoursesupporting
confidence: 78%
“…In a previous analysis of phrases of comparison, Halberg and Teigen (2009) suggested that more than can be regarded as a positive, affirmative phrase, whereas less than signifies a negation (see also Sanford, Dawydiak, & Moxey, 2007). The present study reveals in addition reveals that almost is treated as a positive phrase, despite suggesting upward comparisons with a non-attained reference point.…”
Section: Conversational Implicaturessupporting
confidence: 49%
“…But harnessing loss aversion is only one process that the reframing technique can draw on. Because the framing of probability and quantity estimates affects their communicative content (Halberg & Teigen, ), a reframing intervention can aim at influencing patients' decisions when confronted with health statistics (Gigerenzer, Gaissmaier, Kurz‐Milcke, Schwartz, & Woloshin, ). Whereas strict definitions of framing require equivalence, the term is often also used in a more loose sense including “linguistic redescriptions of the same decision problem” (Krüger, Vogel, & Wänke, p. 13).…”
Section: A Taxonomy Of Choice Architecture Techniquesmentioning
confidence: 99%